FOR A HISTORY OF THE IMPOSSIBLE. THE HISTORY OF PHILOSOPHICAL IDEAS IN WALTER BENJAMIN (UNIV CONCEPCION, BIBLIOTECA CENTRAL, 2016)
This article addresses the place of the history of philosophical ideas in Walter Benjamin's conception of cultural history. From his earlier reflections about the transcendence of the idea, he thinks of the different forms in which diverse historical phenomena always present it partially. After the modern separation of philosophy and literature, the preoccupation for the content of truth of the latter will be more interesting for Benjamin. While modern and bourgeoisie philosophy houses itself in a limited interiority, modern literature exposes the tensions of modernity from a reading that considers the particularity of the literary text, whose content of truth the philosopher might desire from a certain philosophical question that does not impose, on literature, its conceptual schemas.